Public preferences for allocating absolute scarce critical healthcare resources during the COVID-19 pandemic - Pinho, Micaela (2021)
This paper aims to investigate the Portuguese general public views regarding the criteria that should guide critical COVID-19 patients to receive medical devices (ventilators and IUC beds) during the current pandemic context. Based on rationing principles and protocols proposed in ethical and medical literature the authors explore how Portuguese general public evaluates the fairness of five allocation principles: “prognosis”, “severity of health condition”, “patients age”, “instrumental value” (frontline healthcare professionals should be prioritized during the pandemic) and “lottery”.